Coupled flow, stress and damage modelling of interactions between hydraulic fractures and natural fractures in shale gas reservoirs. (2016) - Zhu, Hai-Yan; Jin, Xiao-Chun; Guo, Jian-Chun; An, Feng-Chen; Wang, Yong-Hui; Lai, Xiang-dong
Hydraulic fracturing in naturally fractured shale gas reservoirs is a typical coupled damage and seepage problem. Damage inside natural fractures, caused by either shear stress or tensile stress, can greatly increase the fracture permeability. Additional stress caused by fluid seepage bridges the connectivity among adjacent natural fractures, achieving the stimulated reservoir volume (SRV). The work couples the damage and fluid flow into the Mohr-Coulomb failure criterion for the description of the natural fractures reactivation. Hydraulic fracture is first discretised by the visco-elastic damage pore pressure cohesive elements (PPCE); then by combining the dynamic evolutions of damage, porosity and permeability, a flow, stress and damage (FSD) model of hydraulic fracture and natural fracture system is proposed. The hydraulic stimulation is successful if the permeability of the shale gas reservoir can be improved from the order of nano-Darcy to milli-Darcy. The case study on stimulated reservoir area (SRA) for Q-1 shale gas well in Sichuan Basin agrees with the field data and published data in literatures. [Received: April 6, 2015; Accepted: August 9, 2015]